Guide to teaching puzzle-based learning - Meyer III, Edwin F. (Undergraduate Topics in Computer Science,, 2014)
Puzzle-based Learning is a foundational approach to develop the critical thinking skills and mental stamina essential for solving real-world problems. This Guide to Teaching Puzzle-based Learning provides invaluable insights drawn from the authors' extensive experience in teaching Puzzle-based Learning. Practical advice is provided for teachers and lecturers evaluating a range of different formats for varying class sizes, based on results from classes taught in many different countries. Topics and features: Suggests numerous entertaining puzzles designed to motivate students to think about framing and solving unstructured problems Discusses models for student engagement, setting up puzzle clubs, hosting a puzzle competition, and various warm-up activities Presents an overview of effective teaching approaches used in Puzzle-based Learning, covering a variety of class activities, assignment settings and assessment strategies Examines the issues involved in framing a problem, and reviews a range of problem-solving strategies Contains tips for teachers and notes on common student pitfalls throughout the text Provides a collection of puzzle sets for use during a Puzzle-based Learning event, including puzzles that require probabilistic reasoning, and logic and geometry puzzles This unique textbook/guide will be of great interest to instructors on all levels who wish to experiment with the Puzzle-based Learning approach. This approach has been successfully applied in universities, high schools, professional organizations and leading companies.